Investigations for radiculopathy: The patient perspective. A qualitative, interpretative inquiry. (February 2018) - Ryan, Clare; Roberts, Lisa C.
Abstract: Background: Clinical guidelines recommend that investigations, such as magnetic resonance imaging, are offered only when likely to change management. Meanwhile, the optimal process of diagnosing radiculopathy remains uncertain and, in clinical practice, differences of opinion can occur between patient and clinician regarding the perceived importance of investigations. Objectives: To explore peoples' experiences of investigations and the effect of concordance between clinical presentation and investigation findings. Methods: In this qualitative study, 14 participants who had recently undergone investigations for a clinical presentation of radiculopathy were purposively recruited from an NHS, Primary Care Service in the United Kingdom. Based on the principles of interpretative phenomenological analysis, individual, semi-structured interviews were recorded and transcribed verbatim. Data were managed using a framework approach and analysed thematically. Findings: Although people reported wanting investigations to understand the cause of symptoms and inform management, access to them was reported to be difficult and protracted. When investigations revealed potentially relevant findings, people experienced relief, validation, empowerment and decisive decision-making. Disappointment emerged, however, regarding treatment options and waiting times, and long-term prognosis. When investigations failed to identify relevant findings, people were unable to make sense of their symptoms, relinquish their search to identify the cause, or to move forward in their management. Conclusions: This study provides the first reported in-depth interpretation of peoples' experience of undergoing investigations specifically for radiculopathy. Important implications have been identified for: investigation referral criteria; shared-decision-making; information sharing and managing expectations and disappointment. ClinicalTrials.gov reference: UOS-2307-CR. Highlights: Patients highly valued the informative role of investigations (MRI). Access to investigations was reported to be difficult and protracted. Relevant findings enabled validation, empowerment and decisive decision-making. Non-concordant findings were difficult to understand, or move forward from. Important implications have been identified for policy and clinical practice.